2015
DOI: 10.1021/acs.jafc.5b04337
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cadmium, Iron, and Zinc in Millstreams of Hard Winter Wheat (Triticum aestivum L.)

Abstract: Hard winter wheat (Triticum aestivum L.) is a major crop in the Great Plains of the United States, and our previous work demonstrated that wheat genotypes vary for grain cadmium accumulation with some exceeding the CODEX standard (0.2 mg kg(-1)). Previous reports of cadmium distribution in flour milling fractions have not included high cadmium grain. This study measured the distribution of cadmium, zinc, and iron in flour and bran streams from high cadmium (0.352 mg kg(-1)) grain on a pilot mill that produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 23 publications
2
22
1
Order By: Relevance
“…The extraction of soluble minerals from flour fractions, shorts and bran from gained milling streams and whole grain of each grain cultivar was extracted with Tris-HCl buffer according to procedure described by Guttieri et al [18] with some minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction of soluble minerals from flour fractions, shorts and bran from gained milling streams and whole grain of each grain cultivar was extracted with Tris-HCl buffer according to procedure described by Guttieri et al [18] with some minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Toxic metals compete with other metals for the transport systems in the plant, which explains why they are taken up into the different compartments of the grain. For example, cadmium is stored in the endosperm of wheat, the source of refined flour and to a lesser extent in the outer layers of the grain [ 101 ]. Fungi often colonizes the outer layers of the grains but some can also infect, for example, corn kernels through slit channels.…”
Section: Strategies To Mitigate the Risk Of Contaminants For Humanmentioning
confidence: 99%
“…The categories 'bran and germ' and 'wheat grains and flour' in the EFSA report (2009) have higher Cd concentrations (mean 0.06 and 0.03 mg/kg respectively), as compared to 'wheat products' (mean 0.014 mg/kg). Detailed research has found the highest Cd concentrations in bran and the pollard fractions and the lowest concentrations in wheat grain and flour (Oliver et al, 1993;Guttieri et al, 2015). However, a relation was found between the Cd in the different fractions: Cd concentrations in grains are an effective method to monitor the Cd concentrations in flour and flour products (Oliver et al, 1993).…”
Section: The Effects Of Food Processingmentioning
confidence: 99%
“…In most countries, the varieties differ, which makes comparisons between countries less straightforward. It is also well-known that in non-polluted soils with a low pH (Great Plains of USA), some wheat genotypes (hard winter-wheat) can accumulate Cd in grains and exceed the European limit value (Guttieri et al, 2015).…”
Section: Effects Of CD Containing P-fertilisers On Cd In Soils and Cdmentioning
confidence: 99%